Frontispiece: Exploring the Subtle Effect of Aliphatic Ring Size on Minor Actinide‐Extraction Properties and Metal Ion Speciation in Bis‐1, 2, 4‐Triazine Ligands. Issue 2 (7th January 2020) - Zaytsev, Andrey V.; Bulmer, Rachel; Kozhevnikov, Valery N.; Sims, Mark; Modolo, Giuseppe; Wilden, Andreas; Waddell, Paul G.; Geist, Andreas; Panak, Petra J.; Wessling, Patrik; Lewis, Frank W.
Abstract : Fine tuning the aliphatic ring size of An(III)‐selective bis‐1, 2, 4‐triazine ligands has subtle effects on their extraction and complexation properties. Uncovering the origins of these effects at the molecular level improves our fundamental understanding which in turn can lead to a more rational design of improved ligands. The graphic signifies the iterative nature of this cycle of ligand design. The nuclear power plant in the centre reflects the proposed future application of such ligands for selective An(III) extraction from spent nuclear fuels. For more information, see the Full Paper by F. W. Lewis et al. on page 428 ff.